A Two-Level Preconditioned Conjugate-Gradient Method in Distorted and Structured Grids (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we propose a new two-level preconditioned C-G methodwhich uses the quadratic smoothing and the linear correction in distorted but topologicallystructured grid. The CPU time of this method is less than that of themultigrid preconditioned C-G method (MGCG) using the quadratic element, buttheir accuracy is almost the same. Numerical experiments and eigenvalue analysisare given and the results show that the proposed two-level preconditioned methodis efficient.